2010
DOI: 10.1063/1.3498821
|View full text |Cite
|
Sign up to set email alerts
|

Multilayered Al/CuO thermite formation by reactive magnetron sputtering: Nano versus micro

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
119
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(122 citation statements)
references
References 16 publications
0
119
3
Order By: Relevance
“…Indeed, maximal performances were obtained using an electrostatic NP assembly of Al and Fe 2 O 3 , yielding a comparable heat of reaction of 1800 J g −1 , which is 46 % of the theoretical value. [37] Our results also outperformed the results obtained by physically mixed Al/MoO 3 nanothermite, [38] or by multilayered Al/CuO nanothermite, [39] both methods yielding a heat of reaction of 1200 J g −1 . We have also demonstrated that the onset temperature was reduced from 470 °C to 410 °C using the 80 nm Al NPs instead of the 120 nm NPs.…”
Section: Characterization and Performance Of Dna-assembled Al/cuo Thecontrasting
confidence: 57%
“…Indeed, maximal performances were obtained using an electrostatic NP assembly of Al and Fe 2 O 3 , yielding a comparable heat of reaction of 1800 J g −1 , which is 46 % of the theoretical value. [37] Our results also outperformed the results obtained by physically mixed Al/MoO 3 nanothermite, [38] or by multilayered Al/CuO nanothermite, [39] both methods yielding a heat of reaction of 1200 J g −1 . We have also demonstrated that the onset temperature was reduced from 470 °C to 410 °C using the 80 nm Al NPs instead of the 120 nm NPs.…”
Section: Characterization and Performance Of Dna-assembled Al/cuo Thecontrasting
confidence: 57%
“…Nanothermites also open the perspective to fabricate smaller weapon systems or higher lethality weapon. Moreover, compared to conventional explosives, one asset of nanoenergetic materials is the possible adjustment of the energy density, power release and pressure generation by a suitable choice of fuels, oxidizers, material geometries and reactant compaction [3,[14][15][16][17][18][19][20][21][22]. Until recently, very few reports have considered the dynamic pressures developed by the gas expansion during nanothermites reactions [11,[23][24][25].…”
Section: Introductionmentioning
confidence: 98%
“…More sophisticated assembly methods include, sputtering [1,[20][21][22], arrested reactive milling (ARM) [2,23,24], electrostatic directed assembly [25], and sol-gel synthesis [26,27]. In recent years, self-assembly approaches have been employed to precisely engineer three-dimensional structural nanothermites [28].…”
Section: Introductionmentioning
confidence: 99%